A Family of Finite-Dimensional Representations of Generalized Double Affine Hecke Algebras of Higher Rank - Fu, Y.; Shelley-Abrahamson, S. (Symmetry, Integrability and Geometry: Methods and Applications, 2016)
We give explicit constructions of some finite-dimensional representations of generalized double affine Hecke algebras (GDAHA) of higher rank using R-matrices for Uq(slN). Our construction is motivated by an analogous construction of Silvia Montarani in the rational case. Using the Drinfeld-Kohno theorem for Knizhnik-Zamolodchikov differential equations, we prove that the explicit representations we produce correspond to Montarani's representations under a monodromy functor introduced by Etingof, Gan, and Oblomkov.